Clinical Observations 101: A Video Resource - Helen Morgan; Andrew Ying; Nadine Makki (Association of American Medical Colleges, 2016)
Abstract Introduction The clinical observation or shadowing experience is often a learner's first introduction into the clinical realm. It has been reported that this experience helps promote an understanding of physician roles and workplace challenges. There are currently very limited resources available to help prepare students for this experience. Methods This short video presents, in an engaging cartoon format, the three learning objectives for the premedical clinical observation experience, as defined by the Association of American Medical Colleges. The video is shown on the first day of a year-long course on perspectives in health care in a large lecture setting. Clinical observation experiences are required components of this course. Students were asked to complete an anonymous survey immediately after viewing the clinical observation video. Results We have successfully utilized this video to help prepare 120 first-year undergraduate students for a clinical observation experience since 2014. Based on survey results, students felt that they were better prepared for the clinical observation experience after watching this video. Student comments included the following: "I feel like I am well prepared and understand what is expected of me when I do my observations," "I definitely have a better understanding of what these observations are," and "The video was engaging and got the point across in a direct and quick way." Discussion We have found that this video is an excellent resource for preparing students for the expectations of a clinical observation experience. It provides the opportunity for students to become familiar with the learning objectives of the experience, and of expectations of professionalisms in the clinical setting. The cartoon setting was engaging for the students, and provided a visually appealing vehicle for addressing these issues.